2019
DOI: 10.1016/j.eurpsy.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of emotional lability, mind wandering and sleep quality on ADHD symptom severity in adults with ADHD

Abstract: Mind wandering, emotional lability and sleep quality are currently mostly independently investigated but are all interlinked and play a major role is adult attention-deficit/ hyperactivity disorder (ADHD). Emotional lability is a core feature of the disorder, excessive mind wandering has recently been linked to symptoms and impairments of ADHD and poor sleep quality is experienced by a clear majority of adults with ADHD. All three phenomena lead to functional impairment in ADHD, however their relationship to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 85 publications
(171 reference statements)
4
18
0
Order By: Relevance
“…Finally, we observed a strong correlation between the severity of ADHD symptoms and ED (r = 0.54). In terms of ED, dimensions, negative emotional responses exhibited the strongest correlation with the core ADHD symptoms (r = 0.63) -findings that concur with the literature [16,26,61], and that are also compatible with the study by Graziano & Garcia [9] that reported a stronger correlation between emotional responses and ADHD symptoms in older adolescents.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, we observed a strong correlation between the severity of ADHD symptoms and ED (r = 0.54). In terms of ED, dimensions, negative emotional responses exhibited the strongest correlation with the core ADHD symptoms (r = 0.63) -findings that concur with the literature [16,26,61], and that are also compatible with the study by Graziano & Garcia [9] that reported a stronger correlation between emotional responses and ADHD symptoms in older adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…Distinguishing the dimensions of ED in children with ADHD, they demonstrated that such patients are more likely to experience intense emotions. The authors reported that this association between emotional reactivity and the ADHD symptom burden becomes stronger with age, a finding consistent with published reports acknowledging that ED's impairment persists over the life-span [19,26,27].…”
supporting
confidence: 84%
“…The DMN is characterized by increased activation during rest and mind wandering, and has also been associated with emotional lability (Christoff et al, 2009;Fox et al, 2005;Godwin et al, 2017;Greicius et al, 2003;Martins and Mather, 2016;Mittner et al, 2016;Raichle et al, 2001). Mind wandering has been associated with emotional lability and greater ADHD symptom severity (Helfer et al, 2019). Our finding of reduced FA in the rCAB could speculatively be an anatomical substrate of the frequently observed altered DMN functional connectivity in ADHD, and the associated emotional problems and increased mind wandering that may stem from aberrant activation in the DMN and its connections with the medial temporal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Another observation to emerge from the data is the signi cant association between ADHD and poor sleep quality among drivers, matching previous ndings in the literature. [45][46][47][48][49][50][51][52][53] As proposed by Scarpelli et al, ADHD has an association with macrostructural and microstructural sleep features, which affects the quality of sleep. [45] The interlinked association of poor sleep quality, ADHD, and mind wandering has been investigated in recent studies, which could justify our ndings.…”
Section: Discussionmentioning
confidence: 99%